O trágico: experiência e conceito - Puppi, Ubaldo [UNESP] (Universidade Estadual Paulista (Unesp), Departamento de Filosofia, 1981)
O conceito do trágico está de algum modo liga do à violência. O presente estudo pretende estabelecer a relação essencial vigente entre violência institucional e situação trágica, a situação trágica sendo ao mesmo tempo conseqüência e denúncia da violência institucional. Assim entendido, o trágico é primeiramen te expresso sob forma poética, na arte dramática denominada precisamente tragédia; em seguida , por derivação, sob forma conceitual, na análise da própria realidade histórica. A análise da história atual poderá revelar todo o potencial trágico acumulado na violência do poder.

The concept of the tragic is somehow connected with violence. The present enquiry has the purpose of establishing the essential relationship existing between institutional violence and the tragic situation, the latter being at the same time consequence and denouncement of the former. Understood that way, the tragic is first expressed under a poetical form which is precisely called tragedy in dramatic arts: then under a conceptual form, in the analysis of the historical reality itself, by derivation. The analysis of current history may reveal all the potentiality of the tragic accumulated on the violence of power.
The tragic: experience and concept
Keywords: Trágico; tragédia; violência donúncia poética; denúncia conceitual; Tragic; tragedy; violence of power; endured violence; denounced violence; poetical denouncement; conceptual denouncement